STUDENTS’ PERCEPTION TOWARD THE USE OF VIDEO- RECORDED SPEAKING ASSIGNMENT IN SPEAKING SUBJECT: Descriptive Study at the Sixth Semester Students of English Education Department Muhammadiyah University of Makassar - Paramesti, Ardiya; Sulfasyah; Azis, Awalia (FKIP Unismuh Makassar, 2021)
The purposes of this research are: (1) To know students’ perception toward the use of video-recorded speaking assignment in speaking subject. (2) To find out students’ challenges the use of video-recorded speaking assignment in speaking subject. This research is categorized as quantitative research with took two period of time for the data collection by using questionnaire. The total sample are 46 students used by Purposive Sampling technique. The result of analyze of questionnaire consist of two indicators. Based on the result of this research showed that in table 4.1 the mean 3.29 with Std .49 in level very high (strongly positive), in table 4.2 the mean 2.5 with Std .79 in level Low (Negative). And for the students’ challenges showed that the highest percentage in adequate gadget quality factor with 52,2% or 24 students followed by preparation in conducting material factor with 41,3% or 19 students, and video size to upload factor with 39,1% or 18 students, and the lowest percentage is insufficient knowledge in editing video with 4,3% or 2 students. As a result, the students’ Perception toward the use of video-recorded speaking assignment at Sixth Semester English Education Department of Muhammadiyah University of Makassar categorized was Positive/strongly agree and the dominant challenges factor was inadequate gadget quality